Solar irradiance prediction based on self-attention recursive model network - Kang, Ting; Wang, Huaizhi; Wu, Ting; Peng, Jianchun; Jiang, Hui (Frontiers in Energy Research, 2022)
In recent years, with the continued development and popularity of sustainable energy sources and the increasing utilization of solar energy, accurate solar radiation prediction has become important. In this paper, we propose a new model based on deep learning, Feature-enhanced Gated Recurrent Unit, hereafter referred to as FEGRU, for solar radiation prediction. This model takes the source data with one-dimensional convolution and self-attention to feature attention and processes the data features, and then GRU performs feature extraction on solar irradiance data. Finally, the data dimensionality is transformed by a fully connected layer.The main advantage of FEGRU is that it does not require auxiliary data, but only time series data of solar irradiance can be used for good solar irradiance prediction.Our experiments with solar irradiance samples in Lyon, France, show that our model has better prediction results than the baseline model.